(3QSGdI aj CbSGe GdYdhes - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO abO GdJeSJ efi Cf CTjQ Edi CbSGe GdYdhe ETGQg JLeY Edi GdEjLGR GdceGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B423 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B812 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B86 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHdOjI HGdEScfOQjI (B((3L (B5190) s
Keywords: (3GdeYGQa GdYGeIs